Capacidade de autodepuração no médio e baixo cursos do Rio Uberaba, UPGRH-GD8 - Ferreira, Andrezza Marques (2014)
The multiple uses of water resources has become a difficult task, since the deployment and the continuous improvement of management systems still do not accompany the constant changes that occur in the environment as a function of the anthropic actions. The planning and management of water resources in the watershed scale require use of computational tools that allow the joint modeling of quantity and quality of water in daily and monthly scale. This work of masters had as main objective to evaluate the ability of self-depuration of the middle and lower courses of the river Uberaba (MG), which has strong relevance to water municipalities of Uberaba, Veríssimo, Conceição das Alagoas e Planura (MG). For the period of October 2012 until September 2013, through the AQUATOOL tool, the SIMGES module held the water balance and the GESCAL module simulated quality parameters, dissolved oxygen, biochemical oxygen demand, organic nitrogen, ammonia, nitrate and total phosphorus. In order to make the simulations possible, in twenty sub-sections separated by ten stations of water quality, the coefficients of biochemical reactions were calibrated by the method of trial and error approach. The sensitivity analysis of coefficients Ka, Kd, KNoa and KNai initially calibrated and parameters of quality of the intermediate inputs initially estimated do not present significant variations of water quality in the middle and lower courses of the river Uberaba. The analysis of pollution scenarios, after performing the water balance for the critical flow Q7,10 on every intermediate inputs, it was noted that the parameters nitrate, ammonia and organic nitrogen were in accordance with the limits established in the Normative Deliberation COPAM 01:2008 and the Resolution CONAMA 357:2005. The oxygen parameter dissolved would increase its concentration at 156 %, when compared to the value of the driest month, only in intermediate input that covers the whole urban area of the city of Uberaba (MG) and receiving domestic and industrial effluents without treatment. The parameters DBO5 and Ptotal were the most problematic, which exhibited high values in almost all the inputs, with intermediate exception of the Jataí and Preguiça streams. Thus, it is concluded that the AQUATOOL Tool presented itself favorable in the water management of the Uberaba River s watershed. The topology of the model, deployed in the sub-basin of the Uberaba river in its middle and lower courses, will allow the user of the tool (probably the technician or environmental engineer of the Water and Sewage of Uberaba) to analyze globally or individually, the different aspects of planning and management in this watershed.